ANALISIS FINANSIAL USAHA PEMBIBITAN KELAPA SAWIT DI KABUPATEN LANDAK - BBR, Antonio; Dolorosa, Eva; Aritonang, Marisi (Jurnal Sains Pertanian Equator, 2024)
All of these factors"”economic, social, environmental, legal, and market-related"”are part of the financial feasibility analysis. Because of inflation and other price shocks, businesses must regularly do sensitivity analyses to account for the ever-changing cost and revenue components. This study aims to assess the oil palm nursery company in Landak Regency in terms of its financial viability using sensitivity analysis and investment criteria such as net present value (NPV), internal rate of return (IRR), net benefit to cost (NB/C), and payback period. The method used in this research is a survey method by interviewing respondents with purposive sampling technique. In the NPV Criteria, a value of Rp. 279,800,862 was obtained; In the IRR Criteria, a value of 109% was obtained; In the Net B/C Criteria, a value of Rp. 3.4 was obtained; In the Payback Period Criteria, a value of 1.57 years was obtained; Sensitivity analysis was carried out on the five respondent businesses with a scenario if : There is a 10% decrease in selling prices, a 5% increase in fertilizer prices and even if there is a 10% decrease in selling prices and a 5% increase in fertilizer prices. Of all the criteria analyzed, the results show that the oil palm nursery business in Paloan Village is feasible to run and even developed.